Cigarette smoke condensate modulates migration of human gingival epithelial cells and their interactions with Porphyromonas gingivalis. (5th September 2014) - Imamura, K.; Kokubu, E.; Kita, D.; Ota, K.; Ishihara, K.; Saito, A.
Abstract : Background and Objective: Epithelial cells are recognized as the first line of defense against bacterial infection and environmental harmful stimuli such as cigarette smoke (CS). Although previous studies explored the effects of nicotine on host cells, mechanisms by which CS affects cellular functions remain uncertain. The present study investigated the effects of CS condensate (CSC) on in vitro wound closure of gingival epithelial cells and their potential interactions with a major periodontal pathogen, Porphyromonas gingivalis . Material and Methods: Human gingival epithelial cells (Ca9‐22) were treated with CSC for 24 h. Cell proliferation was determined using a WST‐1 assay. Cell migration was assessed using a wound closure model. The expression of integrins was analyzed by confocal scanning laser microscopy and real‐time PCR. Intracellular invasion of P. gingivalis was evaluated by confocal scanning laser microscopy and an antibiotic protection assay. Results: Low concentrations (1–10 μg/mL) of CSC showed no significant effect on cell proliferation. CSC demonstrated dual effects on epithelial wound closure of Ca9‐22 cells: high concentrations (i.e. 250 μg/mL) significantly inhibited the wound closure whereas low concentrations (i.e. 10 μg/mL) promoted it ( p  <   0.01). CSC induced distinct changes in cytoskeleton. When CSC‐exposed cells were infected with P. gingivalis for 2 h, a significant inhibition of wound closure was observed concurrent with a decrease in integrin α3 expression near the wound area. A significantly increased P. gingivalis invasion into Ca9‐22 was observed when exposed to low concentrations of CSC. Conclusion: Low concentrations of CSC increased invasion of human gingival epithelial cells by P. gingivalis and induced changes in cytoskeleton and integrin expression, thereby modulating the cell migration.